Interdisciplinaridade e contextualização no novo ensino médio: conhecendo obstáculos e desafios no discurso dos professores de ciências - TRINDADE, Inêz Leal (2004)
In this research I discuss the new high school’s challenges for teachers of science mainly the ones which concerns the purpose of learning based in interdisciplinary and contextualization. In face of that, this study was developed in order to answer how teachers are dealing with their practice with the new high school principles and what kind of challenges needs to be faced for the implementation of interdisciplinary and teaching contextualization, from the standpoint of teachers of science. So that I could consider the guiding questions and reach the goals purposed in this study, I used documental research, objecting the reading of the legislation that gave support for the high school reform, and biographic research to observe the central concepts of this research. Besides, I interviewed teachers of Chemistry, Physics and Biology through structural interview. The investigation results showed relative ignorance about the principles of reform established in official documents, for the most of interviewed teachers. However, the teachers didn’t showed themselves inattentive concerning the discussion about interdisciplinary and the contextualization, which not means that these actors reveal complex forms of dealing with these concepts or that they implement consciously made actions, looking for some contextualized and interdisciplinary teaching. It domains, through teacher’s conceptions, an instrumental vision of interdisciplinary and contextualization according to the conceptions pointed up in official texts. Concerning the challenges perceived by teachers to produce the implementation of interdisciplinary and contextualization teaching, those ones remained attached to his context’s dimension, that is, the public school’s structural problems and the limits of space and time. The conceptual dimension of terms in question, as well the limits that come from teacher’s formation, were peripherally observed.